2024
DOI: 10.1002/anie.202317094
|View full text |Cite
|
Sign up to set email alerts
|

Solid State Machinery of Multiple Dynamic Elements in a Metal–Organic Framework

Jacopo Perego,
Andrea Daolio,
Charl X. Bezuidenhout
et al.

Abstract: Engineering coordinated rotational motion in porous architectures enables the fabrication of molecular machines in solids. A flexible two‐fold interpenetrated pillared Metal‐Organic Framework precisely organizes fast mobile elements such as bicyclopentane (BCP) (107Hz regime at 85 K), two distinct pyridyl rotors and E‐azo group involved in pedal‐like motion. Reciprocal sliding of the two sub‐networks, switched by chemical stimuli, modulated the sizes of the channels and finally the overall dynamical machinery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Dynamic machinery of the MOF FTR-P2 (belonging to the family of Frustrated Trigonal Rotors) has been assessed by Perego et al, these molecular dynamics may be due to a guest-stimulated flexibility, and it may well be indicated that FTR-P2 comprises a molecular dynamic of the set of BCP (synthesized by assembly bicyclo[1.1.1]pentane-1,3-dicarboxylate and azpy=4,4'-1,2diazenediylbispyridine), metal nodes, and azo pyridyl pillars [102].…”
Section: Switchable Mofsmentioning
confidence: 99%
“…Dynamic machinery of the MOF FTR-P2 (belonging to the family of Frustrated Trigonal Rotors) has been assessed by Perego et al, these molecular dynamics may be due to a guest-stimulated flexibility, and it may well be indicated that FTR-P2 comprises a molecular dynamic of the set of BCP (synthesized by assembly bicyclo[1.1.1]pentane-1,3-dicarboxylate and azpy=4,4'-1,2diazenediylbispyridine), metal nodes, and azo pyridyl pillars [102].…”
Section: Switchable Mofsmentioning
confidence: 99%